Skeletal Muscle Fiber Size and Gene Expression in the Oldest-Old With Differing Degrees of Mobility - Naro, Fabio; Venturelli, Massimo; Monaco, Lucia; Toniolo, Luana; Muti, Ettore; Milanese, Chiara; Zhao, Jia; Richardson, Russell S.; Schena, Federico; Reggiani, Carlo (Frontiers in Physiology, 2019)
The oldest-old people, in the tenth decade of their life, represent a population characterized by neuromuscular impairment which often implies a loss of mobility and independent life. As recently shown by us (Venturelli et al 2015) and others (Raue et al 2009, Grosicki et al 2016) muscle atrophy and weakness is accompanied by a surprising preservation of the size and the contractile function of the fibers. This suggests that, while most fibers are likely lost with their respective motoneurons, the surviving fibers are well preserved. Here we investigated the mechanisms behind the fiber preservation and the relevance of physical activity. For this reason we compared a group of young healthy controls (Y) with two groups of nonagenarians, one still able to walk (OM) and one confined on wheel chair (OI). We confirmed our previous results and additionally observed a shift in fiber type, towards slow predominance in OM and fast predominance in OI. Myonuclear density was increased in muscles of OI, compared to Y and to OM, a possible a sign of an ongoing atrophy process. We analyzed by Q-RT-PCR the expression of several genes relevant for fiber size and type regulation. In the muscle of all oldest-old both myostatin and IGF-1 expression were reduced compared to Y, however in OI two specific IGF1 isoforms, IGF-1EA and MGF, showed a further significant decrease compared to OM. Surprisingly, also atrogenes (MURF1 and atrogin) expression was significantly reduced compared to Y and this was accompanied a reduction, close to statistical significance of a marker of autophagy, LC3. Among the determinants of the metabolic fiber type, PGC1a was significantly reduced in both OM and OI compared to Y, while AMPK was down-regulated only in OI. We conclude that in contrast to the shift of the balance in favor of pro-atrophy factors found by other studies in older adults (decreased IGF-1, increase of myostatin, increase of atrogenes), in oldest-old also the pro-atrophy factors appear to be down-regulated allowing a partial recovery of the proteostasis balance. The impact of lost or preserved walking ability is limited.